(untitled) (Research, Society and Development, 2025)
Chronic Kidney Disease (CKD) has a high morbidity and mortality rate worldwide, with a prevalence of 7.2% in individuals over 30 years old and between 28 to 46% in individuals over 64 years old. In this sense, the disease presents as asymptomatic or oligosymptomatic in its early stages and becomes evident in advanced stages. Therefore, it is of paramount importance to evaluate the factors that contribute to the development of this comorbidity, considering its multifactorial nature. The objective of the present study is to identify the prevalence of risk factors for CKD in medical students.. This is a cross-sectional observational study of unmatched samples. The study was initiated in 2020, with the collection of initial data, and concluded with a new data collection in 2022. The data were collected through standardized online and in-person questionnaires, containing 11 variables. The study population consisted of medical students from PUC-GO from modules 1 to 8 in the years 2020 and 2022, using convenience sampling. A total of 482 medical students were included in the study. In this way, the following factors were analyzed: age, ethnicity, sex, smoking, body mass index (BMI), arterial hypertension (AH), diabetes mellitus (DM), dyslipidemia, high-protein diet, family history of CKD, and family history of non-communicable chronic diseases. In this regard, there was no significant reduction in the risk factors with the advancement in the medical course. There are possible causes for this, such as increased study workload, limited availability of time for self-care and healthy practices in daily life, and students’ vulnerability to smoking and alcohol consumption, as the majority of students are young and may be influenced by their environment.